Gender as a moderator of the relationship between OCB and turnover intention - Khalid, Shaiful Annuar; Jusoff, Kamaruzaman; Ali, Hassan; Ismail, Mohammad; Mohamed Kassim, Kamsol; Abdul Rahman, Norshimah (Canadian Center of Science and Education, 2009)
This paper examines the relationship between OCBs and turnover intention. The sample consisted of 557 non manager employees across 63 hotels in Malaysia. Managers’ ratings of employees’ OCBs were collected and matched with 557 employees’ self ratings of turnover intention and demographic. Factor analysis of OCB items revealed a new dimension of OCB, labeled as patience, together with four common dimensions - helping behavior, conscientiousness, sportsmanship and civic virtue. Consistent with cognitive consistency theory, the results show that helping behavior, conscientiousness, patience and civic virtue were significantly and negatively related to turnover intention. Moreover, the OCB dimensions explained a meaningful portion (25%) of the turnover intention measure. The results indicated that gender moderated the relationship between helping behavior and turnover intention and this relationship was stronger for females than males. These results point to the importance of considering behavioral factors in effort to predict and manage employee turnover.